Vocational Students' Speaking Challenges and Strategies for Employability: A Qualitative Study - Erni Sriati; Markus Deli Girik Allo; Selvi Panggua (FOSTER: Journal of English Language Teaching, 2026)
This study investigates the challenges vocational students encounter in developing English-speaking skills and self-efficacy, and explores the learning strategies and classroom practices they perceive as helpful for global employability. Employing a qualitative research design with thematic analysis following the Miles and Huberman interactive model, data were collected through in-depth interviews with seven vocational students and classroom observations at a vocational school in Indonesia. The interview protocols captured students' linguistic, affective, and environmental challenges, as well as their perceptions of helpful strategies and practices. The findings revealed eight major speaking challenges: linguistic difficulties in spontaneous speech production; pronunciation and vocabulary barriers; affective barriers including anxiety, fear, and lack of confidence; fear of negative evaluation; peer influence on speaking willingness; insufficient classroom speaking opportunities; limited out-of-class practice; and resource limitations. Students identified eight helpful strategies: utilization of digital media for independent learning; repetition and preparation strategies; pair work and group discussions; structured speaking activities; supportive teacher practices; authentic communication opportunities; supportive classroom environments; and integration of vocational contexts. Classroom observations confirmed limited speaking practice time, student hesitation, and the effectiveness of pair work and teacher modeling. This study contributes to understanding speaking development in vocational contexts by highlighting the interconnected nature of linguistic, affective, social, and environmental challenges. The findings offer practical implications for teachers, curriculum developers, and policymakers seeking to enhance vocational students' oral communication skills for global workforce participation.